2005
DOI: 10.1016/j.cplett.2005.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the temperature and density dependence of the absorption spectra of hydrated electron and solvated silver atom in water

Abstract: We report mixed quantum-classical molecular dynamics simulations of the optical absorption spectrum of the solvated silver atom and electron in liquid water. The simple one electron model is shown to be able to reproduce the strong temperature dependence of the absorption spectra of hydrated electron as well as the much weaker dependence for the silver atom. A qualitative explanation is provided for this experimental fact. When extending these simulations to very low densities corresponding to supercritical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…4 Additional investigations have shown that the mean lifetimes of these clusters, even near the critical density, could be tens of picoseconds. 35, and references therein͒. 16,17 In fact, secondary ͑or "dry"͒ electrons slow down to subexcitation energies and, following thermalization, get localized ͑or "trapped," then forming the so-called "wet" electrons whose exact physical nature is still the subject of investigation͒ and eventually become hydrated ͑for example, see Refs.…”
Section: Effect Of Water Density On the Absorption Maximum Of Hydratementioning
confidence: 99%
“…4 Additional investigations have shown that the mean lifetimes of these clusters, even near the critical density, could be tens of picoseconds. 35, and references therein͒. 16,17 In fact, secondary ͑or "dry"͒ electrons slow down to subexcitation energies and, following thermalization, get localized ͑or "trapped," then forming the so-called "wet" electrons whose exact physical nature is still the subject of investigation͒ and eventually become hydrated ͑for example, see Refs.…”
Section: Effect Of Water Density On the Absorption Maximum Of Hydratementioning
confidence: 99%
“…[24] This solvation shell features a number of molecule ranging from 4 at high water loading, which is the value of ambient-temperature bulk water, to 6 at low water loadings, with a less defined solvation sphere, as is the case for the electron in low-density bulk water. [32] For all the 12 different water loadings simulated here, the hydrated electron is observed to move freely inside the zeolite supercages (diameter ∼ 13Å) and the large twelve-membered rings connecting them (diameter ∼ 7.5Å). During the 360 ps of each simulation, 10 trajectories show the hydrated electron jumping from one supercage to another, including 3 simulations during which the solvated electron visits three different supercages during the run.…”
Section: Structure and Diffusionmentioning
confidence: 99%
“…As was shown by previous studies, the position of the absorption spectrum of the solvated electron in bulk water is strongly influenced by the density of the liquid. [24,32] In particular, lower densities result in a red-shift of the spectrum, due to the larger size of the solvent cavity around the electron. To quantify this effect, we show in Figure 5 the correlation between the maximum of the absorption spectrum and the gyration radius of the hydrated electron for both bulk water at different densities and the zeolite at different water loadings.…”
Section: Absorption Spectrummentioning
confidence: 99%
“…We also investigated the effects of water molecules and an aqueous solution environment on the geometry and stability of the clusters. [50][51][52] Moreover, we studied their effects on electronic excitations with a different number of possible virtual excitation states and compared them with pulse radiolysis experiments. [50][51][52] In this study, we used one water ligand per silver atom/ion for small clusters.…”
Section: Resultsmentioning
confidence: 99%
“…[50][51][52] Moreover, we studied their effects on electronic excitations with a different number of possible virtual excitation states and compared them with pulse radiolysis experiments. [50][51][52] In this study, we used one water ligand per silver atom/ion for small clusters. We understand more water molecules are required to account for first solvation shell of silver species, however, we aimed to understand qualitatively the effect of water ligands as an electron donor on the stabilities and spectra of silver species.…”
Section: Resultsmentioning
confidence: 99%